2008
DOI: 10.1186/1757-1626-1-387
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast lymphoma: a consideration in an HIV patient when a mass is discovered by screening mammography: a case report

Abstract: Primary Breast lymphoma is a rare lesion that has been reported in patients without HIV. However, Primary Breast lymphoma occurring in a patient with HIV has rarely been reported despite the fact that HIV infection is known to increase the propensity to develop certain types of lymphoma. We report a case of an HIV patient with breast lymphoma that was discovered by screening mammography while presenting our argument for more cautionary management in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Occasional cases of bilateral involvementhas also been reported . In this respect, Akinwande et al concluded that multicentricity of the breast NHLs is much more common in HIV‐immunosuppression and high‐grade lymphomas . In the present series, both the patients were suffering from unilateral breast lumps caused by high‐grade DLBCL.…”
Section: Discussionsupporting
confidence: 54%
“…Occasional cases of bilateral involvementhas also been reported . In this respect, Akinwande et al concluded that multicentricity of the breast NHLs is much more common in HIV‐immunosuppression and high‐grade lymphomas . In the present series, both the patients were suffering from unilateral breast lumps caused by high‐grade DLBCL.…”
Section: Discussionsupporting
confidence: 54%